The Influence of Peer Group Method of Education on the Knowledge and Motivation of Pregnant Women in Anemia Prevention - Mariani Mariani; Dodik Hartono; Siti Nur Hasina (Indonesian Journal of Global Health Research, 2024)
Anemia is a nutritional problem that needs attention and is a public health problem in Indonesia. Anemia, which is generally called anemia, is a condition when the body lacks red blood cells or hemoglobin (Hb), where the Hb in the blood is at a level lower than the normal limit. The percentage of pregnant women who experience anemia is 48.9%, this means that around 5 out of 10 pregnant women in Indonesia suffer from anemia. If anemia in pregnant women is not treated, it will result in suboptimal growth and development of the fetus in the womb and has the potential to cause complications in pregnancy and childbirth, even causing maternal death. Objective: This research was conducted to determine "Is there an influence of peer group education on the knowledge and motivation of pregnant women in preventing anemia". This research method uses a pre-experimental design using a one-group pre-post test design method. The population in this study were all pregnant women in the Pajarakan Community Health Center area. The sampling technique used was purpusive sampling, namely selecting samples according to the inclusion criteria, with a sample size of 30 respondents. The data collection instrument uses a questionnaire and validity and reability tests have been carried out with an r table value of 0,747 and cronbach’s alpha 0.757. Analysis uses the Paired simple T-Test. Results The results show that the knowledge and motivation of pregnant women in preventing anemia before and after being given peer group education shows a significant influence where P = 0.000 is smaller than α = 0.005. So that peer group education can be used as a solution to reduce the incidence of anemia in pregnant women.